Pengaruh Penggunaan Media Pembelajaran Powerpoint Pada Pembelajaran Tematik Terhadap Hasil Belajar Kognitif Siswa di Sekolah Dasar Negeri 06 Pontianak Selatan - Achtifah Interavi; Siti Halidjah; Rio Pranata (Departement of Mathematics Education, 2023)
This study aims to analyze the effect of using powerpoint learning media in thematic learning on cognitive learning outcomes of fifth grade students of State Elementary School 06 South Pontianak. The research method used is an experiment with a form of quasi-experimental design, experimental design nonequivalent control group design. uth Pontianak. The sample was determined by probability sampling saturated sampling type, the experimental class and control class were randomly selected by drawing, namely class VA totaling 27 students as the control class and VB totaling 27 students as the experimental class. Data collection techniques using measurement techniques. The instrument used was a multiple choice learning outcome test totaling 40 questions. Based on the calculation of hypothesis testing using SPSS, the tcount is 3.741 with the ttable for the significance level (α = 5% and dk = 27+27-2 = 52) of 1.674689, because the tcount> ttable, Ha is accepted. This proves that there is an effect of using powerpoint learning media in thematic learning on cognitive learning outcomes of fifth grade students of State Elementary School 06 South Pontianak. The results of the calculation of effect size (ES) obtained amounted to 1,03 including high criteria, so it can be concluded that powerpoint learning media in thematic learning has a high influence on the cognitive learning outcomes of grade V students of State Elementary School 06 South Pontianak.